Prevalence of suicidality among the adolescents of a rural municipality of Eastern Terai of Nepal - Bhattarai, Srijana; Thapa, Bijay; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Suicidality is a mental health condition that includes suicidal ideation, plan, and attempt. Prevalence of Suicidality from the pilot study conducted in 2018 in Nepal shows 8.7% among adolescents aged 13 to 17years. The study aimed to determine the prevalence of suicidality among adolescents of a rural municipality of eastern Terai of Nepal.Method: A cross-sectional study was conducted among 443 adolescents from the randomly selected households of a rural municipality of Eastern Terai of Nepal. Validated self-administered tools; suicidal action and plan tools were used to assess the prevalence of suicidality.Result: The study revealed that 30.93% of the adolescent's respondents had developed suicidal thought in the last one year. Similarly, 22.12% of them had made suicidal plan and 12.42% had attempted suicide.Conclusion: High prevalence of suicidality among adolescents indicates need for scaling of mental health awareness programs and services in the rural municipality. Concerned authorities should take an intervention to decrease preventable death among adolescents.